2015
DOI: 10.5505/phd.2015.49091
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cancer Patients’ Information Sources, Information Needs and Expectations of Health Professionals

Abstract: ÖZETAmaç: Bu çalışmanın amacı kanser hastalarının bilgi kaynaklarını, bilgi gereksinimlerini ve sağlık personelinden beklentilerini incelemektir. Gereç ve Yöntem:Araştırma tanımlayıcı olarak yapılmıştır. Araştır-manın örneklemini Türkiye'de en sık kullanılan kanserle ilgili bir bloğun kullanıcıları olan, araştırmaya katılmayı kabul eden 120 kanser hastası oluşturmuştur. Veri toplama aracı olarak araştırmacılar tarafından literatüre dayalı olarak hazırlanan Hastaların Sağlık Personelinden Beklentileri isimli an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In our study, information source of most of the patients having information related to their disease was determined to be the physician and only 12.5% of them answered as nurse for their information source and more than half of them mentioned that the level of information supplied by the health team related to their treatment process was insufficient. Similar to the finding of our study, study of Akgul Baskale et al (2015) mentioned that 82.5% of patients are supplied with information by their physicians and 39.2% was supplied by the nurses (8). As a result of another study, 82% of the patients took information related to the treatment from the physician and the ratio of the ones taking information from nurses was 4% (9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, information source of most of the patients having information related to their disease was determined to be the physician and only 12.5% of them answered as nurse for their information source and more than half of them mentioned that the level of information supplied by the health team related to their treatment process was insufficient. Similar to the finding of our study, study of Akgul Baskale et al (2015) mentioned that 82.5% of patients are supplied with information by their physicians and 39.2% was supplied by the nurses (8). As a result of another study, 82% of the patients took information related to the treatment from the physician and the ratio of the ones taking information from nurses was 4% (9).…”
Section: Discussionsupporting
confidence: 90%
“…Nurses, having information related to the disease process and supplying information to the patients, will increase the trust in the nurses and accordingly this may contribute to the adaptation to the disease. (8). In the study of Cerit (2016), satisfaction of patients from the perspective of nurses was found to be above the average (13).…”
Section: Discussionmentioning
confidence: 99%
“…Some other patients tend to seek information from health care providers to verify their information. Other patients, however, use unreliable resources to get their information (5). As a result, patients who receive chemotherapy treatment are affected negatively by their lack of knowledge and misinformation and this affects their behavior and expectations towards symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…The Patient Information Form: This form was created from 14 questions using different sources (3,5,9). The questions include age, education, marital status, occupation, income status, social security status, number of children, family type, stage of illness, time of disease diagnosis, name and duration of treatment protocol, specific drugs used, and the number of cycles of chemotherapy.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation